INTERNAL AND EXTERNAL FACTORS DETERMINING THE PRICE OFFERING PT MELALI MICE IN WINING BIDDING - Raden Ayu Trisnayoni; I Ketut Sutama; I Ketut Budarma (Politeknik Negeri Bali, 2018)
The research was conducted in PT Melali MICE, one of the biggest MICE’s companies in Indonesia. This research aims are to know the internal and external factors of PT Melali MICE's bid price in winning bidding. Data collection methods used were participatory observation and structured interviews. The analysis technique used is the analysis of Strength, Weakness, Opportunity and Threat (SWOT). The result of the research shows that the internal factors that influence the price determination of PT Melali MICE are the cost, the company's experience and the company's objectives while the external factors affecting the price determination of PT Melali MICE are economic conditions, supply and demand, bidding elasticity, competition and government control. Based on the results of qualitative descriptive analysis and discussion with the management of PT Melali MICE, which makes the main strength is the competitive price, the company has a lot of experience organizing events in various Big Cities in Indonesia and experience of event detail and quality, and the main weakness is not contract with suppliers so that the purchase price is as big as the selling price (not making a profit). the results of discussions with the management of PT Melali MICE, it is known that the main opportunity is the number of international events held in Bali and PT Melali MICE is the leading PCO in Bali, and the main threat faced is the expenditure of the State is more prioritized on the budget in the field of infrastructure, education, health and social assistance